Flexible polygon‐mirror based laser scanning microscope platform for multiphoton in‐vivo imaging. Issue 11 (6th February 2017) - Li, Y. X.; Gautam, V.; Brüstle, A.; Cockburn, I. A.; Daria, V. R.; Gillespie, C.; Gaus, K.; Alt, C.; Lee, W. M.
Abstract : Commercial microscopy systems make use of tandem scanning i.e. either slow or fast scanning. We constructed, for the first time, an advanced control system capable of delivering a dynamic line scanning speed ranging from 2.7 kHz to 27 kHz and achieve variable frame rates from 5 Hz to 50 Hz (512 × 512). The dynamic scanning ability is digitally controlled by a new customized open‐source software named PScan1.0 . This permits manipulation of scanning rates either to gain higher fluorescence signal at slow frame rate without increasing laser power or increase frame rates to capture high speed events. By adjusting imaging speed from 40 Hz to 160 Hz, we capture a range of calcium waves and transient peaks from soma and dendrite of single fluorescence neuron (CAL‐520AM). Motion artifacts arising from respiratory and cardiac motion in small animal imaging reduce quality of real‐time images of single cells in‐vivo. An image registration algorithm, integrated with PScan1.0, was shown to perform both real time and post‐processed motion correction. The improvement is verified by quantification of blood flow rates. This work describes all the steps necessary to develop a high performance and flexible polygon‐mirror based multiphoton microscope system for in‐vivo biological imaging. Abstract : Modern multiphoton microscopy demands the smooth integration of software and hardware so as to conduct cutting edge in‐vivo imaging at single cell level. We introduced an advanced control module capable of freely controlling scanning speed of polygon‐mirror and imaging formats on‐the‐fly. The high dynamic scanning (ms to µs) was used to capture neuron transients and blood flow (mm/s) at single cell level over a large field of view (>500 µm).